Graduate degree completion: Associations with alcohol and marijuana use before and after enrollment. (June 2019) - Allen, Hannah K.; Lilly, Flavius; Beck, Kenneth H.; Vincent, Kathryn B.; Arria, Amelia M.
Abstract: Research has shown that alcohol and marijuana use are associated with academic performance difficulties, but the relationship to completion of a graduate degree has not been explored. Undergraduate students ( n = 1253) were assessed during their first year of college and annually thereafter until age 29. Among the subset of the original sample who enrolled in graduate school ( n = 520), measures of alcohol and marijuana use were averaged separately for the time periods before and after graduate school enrollment. Logistic regression models were developed to examine the associations between these variables and graduate degree completion, adjusting for other factors. In general, a minority of the sample were excessive drinkers or frequent marijuana users. The majority of drinkers (70%) drank an average of twice a week or less each year, and 62% of marijuana users used marijuana once a month or less each year. After adjusting for demographic and program characteristics, marijuana use frequency after graduate school enrollment was negatively associated with odds of graduate degree completion. Alcohol use frequency before graduate school enrollment was positively associated with odds of graduate degree completion. Results add to the growing body of literature on marijuana use and decreased academic achievement, but results should be interpreted with caution given the small, but significant, effect sizes found. The positive association between alcohol use frequency and degree completion might be attributed to engagement in the academic environment. Future studies should examine the potential mechanisms through which alcohol and marijuana use are related to the academic achievement of graduate students. Highlights: Prior research shows that substance use is associated with academic difficulties. This longitudinal study examined substance use and graduate degree completion. A minority of students were excessive drinkers or frequent marijuana users. Marijuana use was associated with decreased odds of completing a graduate degree. Alcohol use was associated with increased odds of completing a graduate degree.